2023
DOI: 10.1109/ojpel.2023.3237709
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Talkative Power Conversion Technologies

Abstract: Power Line Communication (PLC) and Simultaneous Wireless Information and Power Transfer (SWIPT) are popular examples of applications, where power and information are transmitted simultaneously. In most cases, different devices have been used to generate the power and communication signals independently. Usually, the information is superimposed onto the power signal using an external modulator. Recently, power converters have been used to generate pulses not just for power conversion but also for information tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…The terms power talk and talkative power were coined independently of each other in [33] and [39], respectively. We adopt this terminology and refer to talkative power conversion [40]. The talkative power concept can be applied universally in many fields including wireless information and power transfer, not just in electrical grids.…”
Section: Tpc Primermentioning
confidence: 99%
“…The terms power talk and talkative power were coined independently of each other in [33] and [39], respectively. We adopt this terminology and refer to talkative power conversion [40]. The talkative power concept can be applied universally in many fields including wireless information and power transfer, not just in electrical grids.…”
Section: Tpc Primermentioning
confidence: 99%
“…Fig. 1a visualizes the TPC concept [1] using a switchedmode power converter. In addition to the (DC) power conversion, an additional (software-controlled) modulation of the switching signal superimposes a high-frequency signal on the output to transmit data through the power stage.…”
Section: A Talkative Power Conversion (Tpc)mentioning
confidence: 99%
“…8 it is concluded that both modulation strategies enable talkative power, but the hysteretic current control which maintains ZVS conditions, has a wider range of current modulation amplitude before the efficiency decreases. For example, using PWM the efficiency dropped to 99 % already at 1 2 ∆I MOD ≈ 85 mA, while the hysteretic current control has almost a twice as wide range up to 1 2 ∆I MOD ≈ 160 mA. This wide current range enables low bit error rates and high power conversion efficiency for the analog hysteretic current control.…”
Section: Effect Of Modulation Amplitude On Power Efficiencymentioning
confidence: 99%
See 1 more Smart Citation